Food processing cheese production - Satterlee, Lowell D.; Pennsylvania State University.|bDept. of Food Science; Educational Communications, inc.; Pennsylvania State University.|bMedia Sales (University Park, PA Audio-Visual Services, Pennsylvania State University, 1992)
The process of producing cheese from milk is illustrated
Host: Lowell D. Satterlee
Keywords: Cheese factories; Cheese industry; Cheese; Documentary films